Clinical relevance of fibrin fiber diameter during different phases of pregnancy. Issue 10 (22nd July 2016) - Swanepoel, Albe C.
Abstract: Introduction: Pregnancy‐related deep vein thrombosis (DVT) is most common during the late phase of pregnancy and the first 6‐weeks postpartum. Pregnancy‐related DVT can have long‐term complications, specifically post‐thrombotic syndrome (PTS). Fibrin network ultrastructure is altered during pregnancy and post‐partum. It is therefore essential to evaluate fibrin fiber diameter during and after pregnancy as this may provide insight into pregnancy‐related DVT and subsequent PTS. Materials and methods: The fibrin network ultrastructure of females during different phases of pregnancy was compared to that of non‐pregnant females to assess possible changes to the fibrin network morphology and fibrin fiber diameter using scanning electron microscopy micrographs. Results: The fibrin network arrangement was more densely packed during different phases of pregnancy, corresponding to earlier findings. Fibrin diameter decreased significantly during pregnancy, with the greatest decrease occurring during the late phase of pregnancy. The fractal dimensions of fibrin micrographs increased significantly during pregnancy compared to nonpregnant females. These changes are indicative of a simultaneous hypercoagulable and hypofibrinolytic state and correspond to the increased risk of DVT and subsequent development of PTS. Conclusion: It is critical to identify "vulnerable" females with an inflammatory predisposition to prevent possible DVT and subsequent PTS. Modifiable risk factors like obesity and smoking should be addressed to alleviate the burden on the coagulation system. Morphological and viscoelastic techniques are crucial in assessing the coagulatory health of females during pregnancy.